Microstructure Evolution and Strengthening Mechanism of 2 100 MPa Grade Cold-Drawn Steel Wires for Bridge Cables - Yang Xu, Bao Siqian, Kang Xiaolong, Hu Jiarui, Liu Chen, Tian Renming (Teshugang)
The microstructure and strengthening mechanism of 2 100 MPa grade steel wires for bridge cables during cold drawing were studied using a universal tensile testing machine， transmission electron microscope （TEM）， and X-ray diffractometer （XRD）， and the strengthening model suitable for steel wires at low to medium drawing strain was established. The results show that when the stress variable increase to 1.45， the tensile strength and yield strength of cold-drawn steel wires increase from 1 530 MPa and 1 250 MPa of hot-rolled wire rods to 2 185 MPa and 2 041 MPa， respectively， while the elongation decreases from 6.5% to 2.6%. After cold drawing， the dislocation density of ferrite in the steel wires increases and forms dislocation walls. The pearlite colonies turn to the drawing direction to form a fiber texture， and shear bands （S-bands） appear in cementite lamellae with a large angle to the drawing axis. The measured yield strength of steel wires conforms to the interface strengthening and dislocation strengthening models at low and medium drawing strain， with the interface strengthening and dislocation strengthening being 1 359 MPa and 569 MPa， respectively. The contribution ration of interface strengthening decreased from 88% to 68%， while the contribution ratio of dislocation strengthening increased from 6% to 29%. Although the interface strengthening plays a dominant role in the contribution to the yield strength， the growth rate of dislocation strengthening is greater than that of interface strengthening.